IMPLEMENTASI TECHNOLOGY ACCEPTANCE MODEL UNTUK MENGUKUR PENGGUNAAN SISTEM INFORMASI AKADEMIK KAMPUS (SISFOKAMPUS) - Heri Setiawan (Politeknik Negeri Sriwijaya, 2013)
This study aimed to measure use of the campus academic information system (Sisfokampus) with implementation of Technology Acceptance Model. This study uses data collected through a survey of lecturers and employees State Polytechnic Sriwijaya. Sampling method in this study using Simple Random Sampling with a sample of 88 respondents. Data analysis using SPSS for Windows version 19.00 with Path Analysis method. The independent variables were perceived usefulness, ease of use and the attitude of use. While the dependent variable is the behavioral intention and actual use. The results showed that perceptions of usefulness, ease of use simultaneously a significant effect on the attitude of the use of the system. Perception usefulness no significant effect on the attitude of the use of the system. Perceived ease of use significantly influence the attitude of the use of the system. Then, perceived usefulness, ease of use and the attitude of use simultaneously significant effect on system usage intentions. Perception usefulness significantly influence system usage intentions. Ease of use was not a significant effect on system usage intentions. Attitude use significant effect on system usage intentions. Perceptions of usefulness, ease of use, attitudes and intentions use the simultaneous use significant effect on actual usage. The perception usefulness and ease of use in partial no significant effect on actual use. The attitude of use and intention using system partially significant effect on actual usage.